2021
DOI: 10.3390/ani11061506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Apigenin and Astragalus Polysaccharide on the Cryopreservation of Bull Semen

Abstract: The purpose of this study was to determine the effects of apigenin and astragalus polysaccharides on the cryopreservation of bovine semen. Apigenin, astragalus polysaccharides, or their combination were added to a frozen diluent of bovine semen. Afterwards, Computer Assisted Semen Analysis (CASA), membrane functionality, acrosome integrity, mitochondrial integrity, CAT, SOD, GSH-Px, MDA, and ROS detection were conducted. The results showed that adding 0.2 mmol/L AP or 0.5 mg/mL APS could improve the quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The authors noted that API was exceptionally effective for the sperm to acquire better mitochondrial activity, confirming the ability of API to trespass relatively freely through the sperm cell, and thus exhibit its activities intracellularly and have a better protective effect on the mitochondrial membrane. What is more, Wang et al [ 255 ] confirmed that API could reduce bacterial contamination and improve the kinematic parameters and abnormal semen movement in frozen semen as a consequence of bacteriospermia.…”
Section: Apigeninmentioning
confidence: 99%
“…The authors noted that API was exceptionally effective for the sperm to acquire better mitochondrial activity, confirming the ability of API to trespass relatively freely through the sperm cell, and thus exhibit its activities intracellularly and have a better protective effect on the mitochondrial membrane. What is more, Wang et al [ 255 ] confirmed that API could reduce bacterial contamination and improve the kinematic parameters and abnormal semen movement in frozen semen as a consequence of bacteriospermia.…”
Section: Apigeninmentioning
confidence: 99%
“…Semen samples were collected using an artificial vagina twice weekly per bull, in which the cryopreservation and sperm quality assessment were conducted in accordance with the standard commercial procedure (Wang et al, 2021). The criteria for cryopreservation were as follows: semen samples were sent to the laboratory within 30 min at a concentration of at least 1 × 10 9 spermatozoa/ ml, with a sperm motility ≥70% and an abnormality level ≤15%.…”
Section: Bull Semen Collectionmentioning
confidence: 99%
“…For example, a study on bull semen found that adding 0.2 mmol/L of apigenin to the freezing solution improved the sperm ability to move, maintain their shape, and penetrate of the egg. Apigenin also increased the antioxidant activity of the sperm, which helped them resist against oxidative damage caused by freezing and thawing 17 . However, it is important to note that the concentration of apigenin used can have different effects.…”
Section: Introductionmentioning
confidence: 99%
“…It has been studied for its possible benefits in preserving sperm quality during freezing and thawing processes. Some studies have shown that apigenin can improve the survival and function of sperm cells after cryopreservation, especially in bulls and boars 17 , 18 . For example, a study on bull semen found that adding 0.2 mmol/L of apigenin to the freezing solution improved the sperm ability to move, maintain their shape, and penetrate of the egg.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation